Volume 7: Turbomachinery, Parts A, B, and C 2010
DOI: 10.1115/gt2010-22845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inlet Temperature Non-Uniformity on High-Pressure Turbine Performance

Abstract: The temperature of the flow entering a high-pressure turbine stage is inherently non-uniform, as it is produced by several discrete, azimuthally-distributed combustors. In general, however, industrial simulations assume inlet temperature uniformity to simplify the preparation process and reduce computation time In the VI configuration, the hot streaks produced higher time-averaged heat load on the vanes and lower heat load on the blades. As the hot streaks in the VI case passed over the stator vanes, they also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Feng et al found that the second-stage stator exhibits a high efficiency and low thermal load when its clocking position and HS were aligned [6]. Smith found that the time-averaged heat load when the HS is aligned with the stator had a large effect on the stator and a small effect on the rotor compared with the case when the HS is aligned with the stator passage [7]. However, these studies did not consider the effect of axial gap (AG) on the thermal and flow characteristics of the blade surface.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al found that the second-stage stator exhibits a high efficiency and low thermal load when its clocking position and HS were aligned [6]. Smith found that the time-averaged heat load when the HS is aligned with the stator had a large effect on the stator and a small effect on the rotor compared with the case when the HS is aligned with the stator passage [7]. However, these studies did not consider the effect of axial gap (AG) on the thermal and flow characteristics of the blade surface.…”
Section: Introductionmentioning
confidence: 99%
“…A hot-streak positioned on front of the vane LE generates more heat transfer rate than a hot-streak positioned on front of the passage. Smith et al [12] studied numerically the effects of hot-streak clocking position on a HPT stage. They reported that the aligned hot-streak with the vane LE produces higher thermal load on the vanes and lower thermal load on the rotor blades.…”
Section: Effects Of the Hot-streakmentioning
confidence: 99%
“…The isolated effects of the residual swirl only, or the hot-streak only on the aerothermal performance of high-pressure turbines (HPT), are well studied in the literature, on either non-rotating vanes or rotating turbine stages [6][7][8][9][10][11][12][13][14][15][16][17] . Key experimental and computational fluid dynamics (CFD) findings from such isolated effects studies are summarised below.…”
Section: Introductionmentioning
confidence: 99%